Case Report: A familial hematological pedigree reveals VHL germline mutation as a principal predisposition factor with additional mutations modulating phenotypic heterogeneity - Chen, HuiLing; Hu, Wanli; Ma, Chengcheng; Zhang, Miaomiao; Yang, Fuhua; Zeng, Pengyun (Frontiers in Oncology, 2025)
BackgroundVHL germline mutations are classically associated with von Hippel-Lindau syndrome, but their role in hematological malignancies remains underexplored.MethodsWe analyzed a pedigree with acute myeloid leukemia (AML) proband and two offspring: primary immune thrombocytopenia (ITP) and acute T-cell lymphoblastic leukemia (T-ALL) via targeted sequencing and familial validation.ResultsGenetic analysis revealed: (1) the proband carried concurrent VHL, ASXL3, and CCR7 germline mutations along with acquired BCOR/NF1 variants; (2) the ITP-affected offspring inherited ASXL3/CCR7 mutations only; and (3) the T-ALL case exhibited solely the VHL mutation. Acquired mutations (e.g., BCOR/NF1) in the proband suggest a ‘two-hit’ model for leukemogenesis.ConclusionThis study identifies VHL as the principal predisposing mutation in a familial hematologic malignancy pedigree presenting with heterogeneous phenotypes, where ASXL3/CCR7 variants may serve as phenotypic modifiers. These findings advocate for genotype-driven surveillance strategies in familial hematological disorders.